2017
DOI: 10.3945/cdn.117.000430
|View full text |Cite
|
Sign up to set email alerts
|

The Decline in Vitamin Research Funding: A Missed Opportunity?

Abstract: Background: The National Nutrition Research Roadmap has called for support of greater collaborative, interdisciplinary research for multiple areas of nutrition research. However, a substantial reduction in federal funding makes responding to these calls challenging. Objectives: The objectives of this study were to examine temporal trends in research funding and to discuss the potential consequences of these trends. Methods: We searched the NIH RePORTER database to identify NIH research grants and USASpending t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Likewise, the 2022 funding levels for the National Eye Institute was one-third of that of the National Institute of Neurological Disorders And Stroke for example, at $833,012 million vs. $2,503,517 million [239] Despite a recognition that nutrition is the most powerful intervention to reduce disease across the life span, and that correction of micronutrient deficiencies yields substantial returns on investment [10], vitamin research in general, and VK research specifically, has lagged. Chambers et al reported in 2017 that U.S. federal funding for vitamin research declined between 1992-2015 as a percentage of total federal research grant spending [13], from 0.6% to 0.2%, or to $95 million (2016 US dollars). Between the years 2000-2015, VK research had the fewest average projects funded at 8/yr., compared to 115/yr.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the 2022 funding levels for the National Eye Institute was one-third of that of the National Institute of Neurological Disorders And Stroke for example, at $833,012 million vs. $2,503,517 million [239] Despite a recognition that nutrition is the most powerful intervention to reduce disease across the life span, and that correction of micronutrient deficiencies yields substantial returns on investment [10], vitamin research in general, and VK research specifically, has lagged. Chambers et al reported in 2017 that U.S. federal funding for vitamin research declined between 1992-2015 as a percentage of total federal research grant spending [13], from 0.6% to 0.2%, or to $95 million (2016 US dollars). Between the years 2000-2015, VK research had the fewest average projects funded at 8/yr., compared to 115/yr.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a companion paper reporting on the same individuals [48], brain retinol mean pmol/g and (SD) levels were 691. 97 (305.56) and α-tocopherol mean pmol/g and (SD) levels were 66,917 (13,676). The ratios of retinol to MK4 and PK were thus 140 and 1730 respectfully, and that to α-tocopherol were 13,491 and 167,293, both highlighting and reaffirming the low relative tissue levels of VK compared to other fat-soluble vitamins [19].…”
Section: Vitamin K Content and Deliver To Ocular And Related Tissuementioning
confidence: 96%
See 1 more Smart Citation